Protein Lactylation: A new jewel in the crown - Ruby Dhar; Arun Kumar; Subhradip Karmakar (Asian Journal of Medical Sciences, 2025)
Lactylation is a newly identified post-translational modification that has emerged as a crucial epigenetic regulator, significantly influencing cellular functions and disease processes. Lactylation involves the addition of lactate, a glycolysis byproduct, to lysine residues in proteins, particularly histones. This modification, which leads to lactyl-lysine formation, was first discovered in 2019 by Zhang et al. and reported in Nature. What is the Biochemical process: In the lactylation process, lactyl-CoA (derived from lactate) acts as the donor molecule that transfers the lactyl group to the ε-amino group of lysine residues. This marks a unique epigenetic signature that affects gene expression in ways distinct from other histone modifications, such as acetylation or methylation. Lactylation signifies a direct link between cellular metabolism and gene regulation. When cells execute glycolysis and generate lactate, especially under low-oxygen conditions, this triggers histone lactylation. Histone lactylation usually encourages gene expression, akin to acetylation, by facilitating a more accessible chromatin structure. In macrophages, histone lactylation is vital for the late-phase immune response, aiding homeostasis and tissue repair by regulating genes associated with wound healing and bacterial clearance. Abnormal lactylation has been linked to several pathological conditions like Cancer, Inflammatory Diseases, Metabolic Disorders. Recent Research Developments Recent investigations have broadened our knowledge of lactylation beyond histones to non-histone proteins. Researchers have discovered lactylation sites on enzymes associated with glycolysis, the TCA cycle, and additional metabolic pathways, implying a more extensive regulatory network. Advanced mass spectrometry methods have facilitated the mapping of lactylomes across different cell types and tissues, uncovering hundreds of proteins subject to this modification. The identification of lactylation has paved the way for new research opportunities at the crossroads of metabolism and epigenetics. Understanding the enzymes (writers, erasers, readers) involved in regulating lactylation may unveil new therapeutic targets for interventions in diseases linked to metabolic dysregulation and altered gene expression.